Legal and ethical aspects of nursing practice in selected private hospitals in the Western Cape Metropolitan Area - Dorse, Aletta Jacomina (Stellenbosch : University of Stellenbosch, 2008)
Thesis (NCur (Nursing Science))--University of Stellenbosch, 2008.